Total synthesis of the reported structure of ceanothine D via a novel macrocyclization strategy - Lee, Jisun (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
The first total synthesis of the reported structure of ceanothine D, a cyclopeptide alkaloid found in red root, was achieved using a highly convergent synthetic strategy. Highlights of the synthesis include the first concomitant macrocyclization and formation of the unique chiral tertiary alkyl-aryl ether bond with complete regio- and stereo-control in the presence of a sensitive Z-enamide moiety to access the strained para-cyclophane present in its structure. This synthetic strategy may be broadly applicable in the generation of other structurally similar cyclopeptide alkaloids, enabling further biological and chemical investigations.